Source Apportionment and Health Risks of Toxic Metals in Groundwater from a Dual-Aquifer Coal Mine System - Gan Jiang; Kai Chen; Qimeng Liu (Toxics, 2026)
Heavy metal contamination in mining-affected groundwater may pose potential risks to drinking water safety and human health. In this study, 25 groundwater samples, including 18 from Aquifer IV of the Cenozoic unconsolidated porous aquifer system and 7 from the Taiyuan Formation limestone karst aquifer, were collected from the Zhuxianzhuang Coal Mine, Huaibei Coalfield, China. The Heavy Metal Pollution Index (HPI), Metal Index (MI), Positive Matrix Factorization (PMF), and oral-ingestion health risk model were applied to assess metal contamination, source contributions, and human health risks. HPI values ranged from 8.0 to 37.5, with a mean of 21.5, indicating a low overall pollution level. In contrast, MI values suggested cumulative metal contamination, with higher mean values in Taiyuan Formation limestone karst groundwater (5.60) than in Aquifer IV groundwater (2.38). PMF identified two major factors, interpreted as a natural water–rock interaction source and a combined anthropogenic and mining-related source. Health risks were consistently higher in Taiyuan Formation limestone karst groundwater. Non-carcinogenic risks were higher for children and mainly controlled by As, whereas carcinogenic risks were higher for adults and mainly associated with Cr. These findings highlight the need for aquifer-specific monitoring and source control to reduce toxic metal exposure in coal mining areas.